Analysis of Rice Husks and Sugarcane Bagasse for Water Treatment of Formation Water in Oil Fields - Aqlyna Fattahanisa; Listiana Satiawati; Lisa Samura (International Journal of Science and Environment (IJSE), 2025)
In the oil and gas production process in the Cepu field, oil, gas, and water are produced. After oil and gas are produced from the reservoir to the surface, the water that is produced will be returned to the environment. In this water, there is a relatively small amount of oil, high total dissolved solids (TDS), and low pH. High TDS can cause hardness in the water to increase, pH that is too acidic and alkaline can cause pollution to the environment, also residual oil in the water can damage the environment because it is difficult to combine and difficult to decompose. Therefore, this problem can be overcome one way by the adsorption process. This research aims to test absorption using an adsorbent in the form of activated carbon. This adsorption uses sugar cane bagasse and rice husks which can be obtained at low prices and also in abundance. Several stages carried out in this research were making activated carbon by drying the bagasse and rice husks, then blending it until smooth, then placing it in a furnace at a temperature of 800℃. Produced water in Cepu has a TDS value of 5100 ppm and a pH of 5. By adding sugarcane bagasse and rice husk adsorbent the pH value becomes 7, then the TDS value becomes 2261 ppm after adding 3 grams of rice husk adsorbent. and the TDS value became 1153 ppm with the addition of 3 grams of sugarcane bagasse adsorbent. The results of this research provide evidence of the effectiveness of sugarcane bagasse and rice husks as adsorbents in reducing TDS values, pH, and absorbing residual oil from produced water so that it complies with the quality standards of Minister of Environment Regulation (PermenLH) Number 19 of 2010.